2002
DOI: 10.1557/proc-744-m8.32
|View full text |Cite
|
Sign up to set email alerts
|

Optical and EPR Study of Defects in Cadmium Germanium Arsenide

Abstract: Bulk crystals of CdGeAs 2 have been characterized using photoluminescence (PL), optical absorption, Hall effect, and electron paramagnetic resonance (EPR) techniques. An absorption band near 5.5 microns at room temperature is observed in all of the p-type samples we have studied. A correlation between the magnitude of this optical absorption and the excess hole concentration at room temperature is established. Also, an EPR signal is found to correlate with the strength of this absorption band. PL data are cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…The shallow acceptor, therefore, appears to play an important part in this absorption process by forming empty states in the upper band. Based on EPR results, the shallow acceptors are likely due to the antisite defect Ge As [19,20]. The deep acceptor may be a V Cd or V Cd complex [21].…”
Section: Impurities and Dopantsmentioning
confidence: 99%
“…The shallow acceptor, therefore, appears to play an important part in this absorption process by forming empty states in the upper band. Based on EPR results, the shallow acceptors are likely due to the antisite defect Ge As [19,20]. The deep acceptor may be a V Cd or V Cd complex [21].…”
Section: Impurities and Dopantsmentioning
confidence: 99%
“…The empty states in the upper valence band are formed by a shallow acceptor. Moreover, electron paramagnetic resonance (EPR) measurements suggested that the point defects responsible for the shallow acceptor may be associated with germanium on arsenic sites [16]. However, the situation is more complex as the crystals can contain a variety of defects which interact one another.…”
Section: Introductionmentioning
confidence: 99%
“…Although the difference in energy at k ¼ 0 between the top two valence bands is about 0.16 eV, it has been theoretically shown [6] that the peak of the transition between the two upper valence bands will occur closer to 0.22 eV, in agreement with the experimental data. From our earlier study [7], the 5.5 lm absorption band is highly polarized with the intensity taken with Ekc being approximately three times larger than the intensity taken with E ? c. A correlation between the absorption magnitude and hole concentration at room temperature has been established [5,7].…”
Section: Introductionmentioning
confidence: 77%
“…From our earlier study [7], the 5.5 lm absorption band is highly polarized with the intensity taken with Ekc being approximately three times larger than the intensity taken with E ? c. A correlation between the absorption magnitude and hole concentration at room temperature has been established [5,7]. An electron paramagnetic resonance (EPR) signal attributed to a shallow acceptor, suggested to be the germanium-on-arsenic antisite defect, has also been correlated with the absorption intensity [7].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation